Ortho-aryl substituted DPEphos ligands: rhodium complexes featuring C–H anagostic interactions and B–H agostic bonds. Issue 25 (2nd June 2021) - Race, James J.; Burnage, Arron L.; Boyd, Timothy M.; Heyam, Alex; Martínez-Martínez, Antonio J.; Macgregor, Stuart A.; Weller, Andrew S.
Abstract : Rh(i ) complexes of ortho -substituted DPEphos-R (R = H, Me, OMe, i Pr) ligands show anagostic interactions; for R = i Pr C–H activation/dehydrogenative borylation forms a product exhibiting both B–H/Rh 3c-2e agostic and C–H/Rh anagostic motifs. Abstract : The synthesis of new Schrock–Osborn Rh(i ) pre-catalysts with ortho -substituted DPEphos ligands, [Rh(DPEphos-R)(NBD)][BAr F 4 ] [R = Me, OMe, i Pr; Ar F = 3, 5-(CF3 )2 C6 H3 ], is described. Along with the previously reported R = H variant, variable temperature 1 H NMR spectroscopic and single-crystal X-ray diffraction studies show that these all have axial (C–H)⋯Rh anagostic interactions relative to the d 8 pseudo square planar metal centres, that also result in corresponding downfield chemical shifts. Analysis by NBO, QTAIM and NCI methods shows these to be only very weak C–H⋯Rh bonding interactions, the magnitudes of which do not correlate with the observed chemical shifts. Instead, as informed by Scherer's approach, it is the topological positioning of the C–H bond with regard to the metal centre that is important. For [Rh(DPEphos– i Pr)(NBD)][BAr F 4 ] addition of H2 results in a Rh(iii ) i Pr–C–H activated product, [Rh(κ 3, σ-P, O, P-DPEphos- i Pr′)(H)][BAr F 4 ]. This undergoes H/D exchange with D2 at the i Pr groups, reacts with CO or NBD to return Rh(i ) products, and reaction with H3 B·NMe3 / tert -butylethene results in a dehydrogenative borylation to form a complex that shows both a non-classical B–H⋯Rh 3c-2e agostic bond and a C–H⋯Rh anagostic interaction at the same metal centre.